Algunos factores socioculturales y cuidado de la salud de la familia desde la perspectiva de genero. Distrito Victor Larco, 2007 - Bulnes Goicochea, Lady Joanna (2007)
This quantitative, descriptive, and transverse research work was done in Vista Alegre neighborhood, Victor Larco district during the months of August through October 2007; it had the purpose of determining the relation of some social – cultural factors about the family healthcare since the genre perspective. The sample was formed by 135 families with fulfilled the inclusion criterions, the entire sample was formed by all the families who live in Vista Alegre neighborhood. The information that we got was through the scale instrument about the family healthcare since the genre perspective, which was based on Scott genre theories. The trustworthy test of Cronbach Alpha was 0.672. The chi-square (X2) and the statistical text Eta were used to analyze the data. The scores show that there is the genre perspective about the healthcare in 36.3 percent and there is not genre perspective about the family healthcare in 63.7 percent. Moreover there is a relation among the social – cultural factors: family life cycle, education grade, married status, occupation and relation with the family healthcare since the genre perspective and there is not significative relation among the social – cultural factors: kind of family, size of family and family incomes with the family healthcare since the genre perspective.